2019
DOI: 10.1155/2019/4608165
|View full text |Cite
|
Sign up to set email alerts
|

AT1R-Mediated Apoptosis of Bone Marrow Mesenchymal Stem Cells Is Associated with mtROS Production and mtDNA Reduction

Abstract: Angiotensin II (Ang II) is used as an inducer for the differentiation of mesenchymal stem cells (MSCs). Whether the commonly used doses of Ang II for MSC differentiation affect cell apoptosis has not been elucidated. In this study, we investigated the effect of Ang II on the apoptosis of bone marrow MSCs (BMMSCs), and its relations to the activation of Ang II receptor-1- (AT1R-) signaling, mitochondrial ROS (mtROS) generation, and mitochondrial DNA (mtDNA) leakage. AT1R expression in BMMSCs was identified by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Ang II and its receptor (AT1R) have been reported to induce NADPH oxidase (NOX)-dependent oxidative stress, generating ROS in osteoclasts (Nguyen Dinh Cat et al, 2013;Zhang et al, 2019;Zhou et al, 2020). In our present study, we found that azilsartan, an AT1R blocker, suppressed intramitochondrial and intracellular ROS production in osteoclasts.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Ang II and its receptor (AT1R) have been reported to induce NADPH oxidase (NOX)-dependent oxidative stress, generating ROS in osteoclasts (Nguyen Dinh Cat et al, 2013;Zhang et al, 2019;Zhou et al, 2020). In our present study, we found that azilsartan, an AT1R blocker, suppressed intramitochondrial and intracellular ROS production in osteoclasts.…”
Section: Discussionsupporting
confidence: 55%
“…Angiotensin (Ang) II, an octapeptide component of the reninangiotensin system (RAS), exerts its effects through two pharmacologically different G protein-coupled receptors: AT1R and AT2R (de Cavanagh et al, 2004;Benigni et al, 2010). Previous studies have documented the local expression of AT1R in the skeletal system of humans and animals (Zhang et al, 2019). Several components of the RAS, such as AT1R, AT2R, and ACE, are upregulated in mouse calvarial tissue during titanium-induced osteolysis (Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…ROS level frequently indicates intracellular oxidative conditions. Previous studies have revealed that Ang II could induce the release of reactive oxygen species (ROS) in cardiovascular diseases [ 28 ]. During IDD, excessive production of intracellular ROS will accelerate NP cell damage and inflammatory response [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ang II could increase mitochondrial ROS through the activation of Nox2. In a study, Ang II at the dose of 1 and 10 μM leads to apoptosis in bone marrow-derived MSCs due to mitochondrial ROS production and mitochondrial DNA leakage mediated via AT 1 R. Treatment with AT 1 R inhibitor, losartan, markedly inhibited the Ang II-induced apoptosis and mitochondrial ROS ( Zhang F. et al, 2019 ). Ang II production by cleaving enzyme chymase is several times higher in bone marrow than in other tissues.…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%